The Paradox of Communication Professionals: Identifying the Gap between Theory and Practice and its Determining Factors - Jakučionienė, Lina (Information & Media, 2023)
Researchers emphasize the need for communication to be part of the strategic management of an organization and its importance to the organization is recognized, yet the role of communication as a success and value creator for business organizations is not appreciated. This paper presents a study that aims to explore the perception of the role of communication professionals from the perspective of CEOs of business organizations. Semi-structured individual interviews were used to gather the views of CEOs of business organizations. The results of the research revealed a paradox that has not been explored so far. While CEOs of business organizations do not see top-level communication professionals as technical staff, but rather as having a strategic advisory role, the need of CEOs for the capabilities of communication professionals in the strategy development process is more of a technical operational rather than a strategic nature. CEOs tend to ignore the core mission of strategic communication which is to align the communication strategy with the business organization’s strategy. The traditional view of the role of communication professionals leads to the perception that communication professionals are not perceived as important strategists in the development and implementation of the business organization’s strategy.